The Bible View of Slavery Reconsidered. A Letter to the Right Rev. Bishop Hopkins. - Anonymous [Biblicus] (My University, 1863)
[Biblicus] 1863. "The Bible View of Slavery Reconsidered: A Letter to the Right Rev. Bishop Hopkins" 2nd.Ed. (Philadelphia: Henry B. Ashmead, Book and Job Printer, 1863). http://hdl.handle.net/10428/471. A letter arguing against the pro-slavery views of the Bible expressed by Rev. Bishop John Hopkins. MS/146-007 Slavery Papers, Speeches & Manuscripts
Keywords: Slavery and the Church -- United States -- History; Slavery